2015
DOI: 10.1111/jzo.12306
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of flight initiation distance in Eurasian red squirrels in urban versus rural habitat

Abstract: Urbanization has caused significant behavioural modifications in wild animals. Change in anti-predator behaviour is the most widespread example across different taxa in urban areas, which is probably due to a decrease in predation pressure and habituation towards humans. Seasonality or phenology has also been modified by urbanization since some resources in urban environments are highly controlled, for example, artificial feeding. Under natural conditions, anti-predator responses vary with seasonal variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
72
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 50 publications
6
72
1
1
Order By: Relevance
“…Among many factors, predator-prey interactions, are one of the key mechanistic processes in community assembly (Lima 1998, Chase et al 2002, that are known to be affected by urbanization (e.g., Møller and Ib añez-A lamo 2012, D ıaz et al 2013, Uchida et al 2016, E€ otv€ os et al 2018; consequently, they are candidates for explaining the differential effects of land-sharing and landsparing development approaches on biodiversity. For example, Shochat et al (2006) have suggested that predation could be one of the main factors modifying the urban assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…Among many factors, predator-prey interactions, are one of the key mechanistic processes in community assembly (Lima 1998, Chase et al 2002, that are known to be affected by urbanization (e.g., Møller and Ib añez-A lamo 2012, D ıaz et al 2013, Uchida et al 2016, E€ otv€ os et al 2018; consequently, they are candidates for explaining the differential effects of land-sharing and landsparing development approaches on biodiversity. For example, Shochat et al (2006) have suggested that predation could be one of the main factors modifying the urban assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…, Uchida et al. , Eötvös et al. ); consequently, they are candidates for explaining the differential effects of land‐sharing and land‐sparing development approaches on biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Humans in cities seldom pose direct threat to free‐living animals like birds (Clucas & Marzluff, ); thus, greater risk‐taking (e.g., reduced avoidance) toward humans can be advantageous in urban habitats. Reduced flight responses have been observed in many urban animals (Samia, Nakagawa, Nomura, Rangel, & Blumstein, ), including birds (Carrete & Tella, ; Møller et al, ; Myers & Hyman, ; Vincze et al, ), mammals (McCleery, ; Uchida, Suzuki, Shimamoto, Yanagawa, & Koizumi, ), and reptiles (Lapiedra, Chejanovski, & Kolbe, ; McGowan, Patel, Stroh, & Blumstein, ).…”
Section: Introductionmentioning
confidence: 99%